Impact of Chronic PVC Burden on Left Ventricular Function and Cardiovascular Outcomes - Hameed Ullah; Khan, Muhammad Niaz; Waris, Abdul; Nazeef Ullah; Abid Ullah; Saeed, Ihtisham (Indus Journal of Bioscience Research, 2025)
Objective: To evaluate the impact of chronic premature ventricular complex (PVC) burden on left ventricular (LV) function and cardiovascular outcomes, and to assess the role of pharmacological treatment in improving clinical outcomes. Methodology: This retrospective study was conducted at the Department of Cardiac Electrophysiology, Hayatabad Medical Complex, Peshawar, from September 2023 to July 2024. A total of 250 patients were included, divided into high PVC burden (>20%) and low PVC burden (≤20%) groups, with 125 patients in each group. Data on PVC burden, LV ejection fraction (LVEF), left atrial volume index (LAVI), and follow-up outcomes were collected. Statistical analysis included chi-square and t-tests, with significance set at p < 0.05. Results: The high PVC burden group showed significantly lower mean LVEF (42%) compared to the low PVC burden group (56%) (p < 0.001). LAVI was markedly higher in the high-burden group (34.5 mL/m² vs. 24.3 mL/m², p < 0.05). Follow-up outcomes were significantly associated with medication use; 68% of patients on medication improved, compared to 40% without medication (p < 0.05). A chi-square test revealed significant association between medication use and follow-up outcomes (p = 0.02). Conclusion: Chronic PVC burden adversely affects LV function and cardiovascular outcomes. Pharmacological treatment significantly improves clinical outcomes, underscoring the need for structured management strategies. Future research should focus on prospective studies and randomized trials to validate these findings.